2020
DOI: 10.1111/cea.13747
|View full text |Cite
|
Sign up to set email alerts
|

Impaired small airway function in non‐asthmatic chronic rhinosinusitis with nasal polyps

Abstract: Background: There is clinical evidence for impaired lung function in chronic rhinosinusitis with nasal polyps (CRSwNP) patients, which may be due to a high incidence of asthma comorbidity. The lung function characteristics of non-asthmatic CRSwNP patients are not known. Small airway dysfunction (SAD) is involved in the pathogenesis of asthma. However, whether SAD is detected in non-asthmatic patients with CRSwNPs remains unclear. Objective: This study analysed the lung function of non-asthmatic patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…We have finally entered the much‐anticipated era of personalized medicine for asthma, and several articles evaluated biologics and the variation in individual response to these in people with asthma 25‐27 , 28‐36 , 37 , 38 Others evaluated more traditional treatments for asthma, such as corticosteroids or mechanisms that may underlie impaired airway function in asthma 39‐59 . New interventions studied in clinical trials included air cleaners, triple inhaler therapy, an oral prostaglandin D2 antagonist 60‐62 and other more preliminary data from various interventions, from cinnamon and bacterial peptides to allergen immunotherapy 63‐67 .…”
Section: Asthmamentioning
confidence: 99%
“…We have finally entered the much‐anticipated era of personalized medicine for asthma, and several articles evaluated biologics and the variation in individual response to these in people with asthma 25‐27 , 28‐36 , 37 , 38 Others evaluated more traditional treatments for asthma, such as corticosteroids or mechanisms that may underlie impaired airway function in asthma 39‐59 . New interventions studied in clinical trials included air cleaners, triple inhaler therapy, an oral prostaglandin D2 antagonist 60‐62 and other more preliminary data from various interventions, from cinnamon and bacterial peptides to allergen immunotherapy 63‐67 .…”
Section: Asthmamentioning
confidence: 99%
“…An increasing number of studies have provided consistent evidence that asthma is closely related to chronic rhinosinusitis (CRS), thus strongly supporting the united airway concept [ 4 , 5 ]. Indeed, about 50% of patients with CRS have comorbid asthma, whereas 40 ~ 75% of patients with asthma have comorbid CRS [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, about 50% of patients with CRS have comorbid asthma, whereas 40 ~ 75% of patients with asthma have comorbid CRS [ 3 , 6 ]. Although there is no direct evidence of causality between the two conditions, a direct correlation has nevertheless been found between CRS severity and asthma severity [ 4 , 7 ]. Although a recent study by Wu and colleagues [ 8 ] has demonstrated that the clinical phenotypes of patients with both nasal polyps and comorbid asthma (NPcA) could be divided into 3 clusters, mainly according to onset, duration and severity of symptoms, studies investigating phenotypes of asthma based on CRS comorbidity, severity of airflow obstruction and airway inflammation, and inflammation type of asthma using cluster analysis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Compared with CRSsNP, CRSwNP manifests a higher disease severity and a higher risk of asthma comorbidity, and also showed a high risk for recurrence. 3 , 4 CRSwNP is characterized by the formation of edematous stroma and pseudocysts. 5 Evidence shows that tissue remodeling is one of the main causes of the formation of nasal polyps.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic rhinosinusitis with nasal polyps (CRSwNP) in Europe is estimated to be between 2.1% (France) and 4.4% (Finland) and is 4.2% in the United States 1 . Compared with CRSsNP, CRSwNP manifests a higher disease severity and a higher risk of asthma comorbidity, and also showed a high risk for recurrence 3,4 . CRSwNP is characterized by the formation of edematous stroma and pseudocysts 5 .…”
Section: Introductionmentioning
confidence: 99%